Camera trapping of Grey-faced Petrel (Pterodroma gouldi) breeding burrows reveals interactions with introduced mammals throughout the breeding season. (2nd October 2019) - Stolpmann, Lea M.; Landers, Todd J.; Russell, James C.
ABSTRACT: Grey-faced Petrels ( Pterodroma gouldi ) are burrow-nesting seabirds endemic to New Zealand. They usually breed on mammal-free offshore islands along the North Island coast. Mechanisms by which breeding colonies can persist on the North Island with introduced mammals present are still uncertain. Motion-sensing video cameras were used in the Waitakere Ranges to determine the types of interaction between resident introduced mammal species and petrel breeding burrows. Existing predator control is reducing the total count of recorded interactions by predators, with rabbits ( Oryctolagus cuniculus ) entering burrows dominating interactions. The interaction of ship rats ( Rattus rattus ) or rabbits with breeding burrows had no influence on egg-laying or chick-hatching success. Grey-faced Petrels remained in breeding burrows, despite high interaction frequencies of introduced mammals prior to the egg-laying stage. Whilst our data show no impact of mammalian visit rates on Grey-faced Petrel breeding success, other published studies suggest that population recovery might be enhanced by site-specific trapping and baiting methods which also target rabbits.